2023
DOI: 10.1002/smll.202303247
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Emission Linewidth of Pure‐Blue ZnSeTe Quantum Dots through Shell Engineering toward High Color Purity Light‐Emitting Diodes

Abstract: High color purity blue quantum dot light‐emitting diodes (QLEDs) have great potential applications in the field of ultra‐high‐definition display. However, the realization of eco‐friendly pure‐blue QLEDs with a narrow emission linewidth for high color purity remains a significant challenge. Herein, a strategy for fabricating high color purity and efficient pure‐blue QLEDs based on ZnSeTe/ZnSe/ZnS quantum dots (QDs) is presented. It is found that by finely controlling the internal ZnSe shell thickness of the QDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The QDs with thin ZnSe inner shell layer (QD-H1) showed a fast decay process as well as apparent bleach of absorption peaks (PB1), whereas the QDs with thick ZnSe inner shell layer (QD-H2) possessed a slow decay process and the absorption peaks (PB2) barely bleached. 59 As the thickness of the ZnSe inner shell layer further increased, the decay process was accelerated, and the absorption peaks bleached apparently again, as documented in their work. These phenomena indicate that for both InP-based QDs and ZnSeTe-based QDs, with suitable thickness of inner shell layer, the lattice strain could be balanced and diminished the interfacial defects, thereby improving their optical performances.…”
Section: Optical Properties Of Qds With Different Inner Shell Thicknessmentioning
confidence: 61%
See 3 more Smart Citations
“…The QDs with thin ZnSe inner shell layer (QD-H1) showed a fast decay process as well as apparent bleach of absorption peaks (PB1), whereas the QDs with thick ZnSe inner shell layer (QD-H2) possessed a slow decay process and the absorption peaks (PB2) barely bleached. 59 As the thickness of the ZnSe inner shell layer further increased, the decay process was accelerated, and the absorption peaks bleached apparently again, as documented in their work. These phenomena indicate that for both InP-based QDs and ZnSeTe-based QDs, with suitable thickness of inner shell layer, the lattice strain could be balanced and diminished the interfacial defects, thereby improving their optical performances.…”
Section: Optical Properties Of Qds With Different Inner Shell Thicknessmentioning
confidence: 61%
“…Furthermore, the transient absorption spectra of ZnSeTe-based QDs with a series of different thicknesses of the ZnSe inner shell layer exhibited distinct features and decay process (Figure l–n). The QDs with thin ZnSe inner shell layer (QD-H1) showed a fast decay process as well as apparent bleach of absorption peaks (PB1), whereas the QDs with thick ZnSe inner shell layer (QD-H2) possessed a slow decay process and the absorption peaks (PB2) barely bleached . As the thickness of the ZnSe inner shell layer further increased, the decay process was accelerated, and the absorption peaks bleached apparently again, as documented in their work.…”
Section: Optical Properties Of Qds With Different Inner Shell Thicknessmentioning
confidence: 68%
See 2 more Smart Citations
“…Zhao et al attributed the observed line width narrowing to the suppression of defect-related carrier trapping and exciton− phonon coupling by the ZnSe thick shell beyond a certain threshold. 50 Conversely, an excessively thick ZnSe shell introduces additional trap sites, leading to an expansion of fwhm and diminished PL QY. The influence of ZnSe shell thickness on PL properties was investigated by analyzing timeresolved PL decay profiles of ZnSeTe/ZnSe/ZnS QDs with varying inner ZnSe shell thickness (Figure 4b).…”
mentioning
confidence: 99%